The genome of an Encephalitozoon cuniculi type III strain reveals insights into the genetic diversity and mode of reproduction of a ubiquitous vertebrate pathogen - Pelin, A; Moteshareie, H; Sak, B; Selman, M; Naor, A; Eyahpaise, M-È; Farinelli, L; Golshani, A; Kvac, M; Corradi, N (Heredity, 2016)
Encephalitozoon cuniculi is a model microsporidian species with a mononucleate nucleus and a genome that has been extensively studied. To date, analyses of genome diversity have revealed the existence of four genotypes in E. cuniculi (EcI, II, III and IV). Genome sequences are available for EcI, II and III, and are all very divergent, possibly diploid and genetically homogeneous. The mechanisms that cause low genetic diversity in E. cuniculi (for example, selfing, inbreeding or a combination of both), as well as the degree of genetic variation in their natural populations, have been hard to assess because genome data have been so far gathered from laboratory-propagated strains. In this study, we aim to tackle this issue by analyzing the complete genome sequence of a natural strain of E. cuniculi isolated in 2013 from a steppe lemming. The strain belongs to the EcIII genotype and has been designated EcIII-L. The EcIII-L genome sequence harbors genomic features intermediate to known genomes of II and III lab strains, and we provide primers that differentiate the three E. cuniculi genotypes using a single PCR. Surprisingly, the EcIII-L genome is also highly homogeneous, harbors signatures of heterozygosity and also one strain-specific single-nucleotide polymorphism (SNP) that introduces a stop codon in a key meiosis gene, Spo11. Functional analyses using a heterologous system demonstrate that this SNP leads to a deficient meiosis in a model fungus. This indicates that EcIII-L meiotic machinery may be presently broken. Overall, our findings reveal previously unsuspected genome diversity in E. cuniculi, some of which appears to affect genes of primary importance for the biology of this pathogen.
Keywords: heterozygot; DNA, Fungal; Chromosome Mapping; Heterozygote; genetická variace; Genotype; Sequence Analysis, DNA; sekvenční analýza DNA; Genome, Fungal; genom fungální; Meiosis; jednonukleotidový polymorfismus; DNA fungální; meióza; Animals; Polymorphism, Single Nucleotide; Encephalitozoon cuniculi; mapování chromozomů; zvířata; Arvicolinae; genotyp; Genetic Variation